2016
DOI: 10.1302/0301-620x.98b6.37208
|View full text |Cite|
|
Sign up to set email alerts
|

The influence of a history of clinical depression on peri-operative outcomes in elective total shoulder arthroplasty

Abstract: The awareness that clinical depression is associated with increased complications following total shoulder arthroplasty provides physicians an opportunity for early intervention in this at-risk population. Cite this article: Bone Joint J 2016;98-B:818-24.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 46 publications
3
49
0
Order By: Relevance
“…In another prospective study of 485 elderly men undergoing transurethral prostatectomy for benign prostatic hyperplasia, Tai et al 16 showed that patients with a higher Geriatric Depression Scale (GDS) score were significantly more likely to develop postoperative delirium. Similarly, in a retrospective study of 224,060 patients undergoing elective total shoulder arthroplasty between 2002 and 2012, Mollon et al 10 showed depression to be an independent risk factor for postoperative delirium. In another retrospective analysis of 91 patients (age ≥ 75 years) who underwent esophagectomy for the treatment of esophageal cancer, Yamamoto et al 20 showed that GDS score was independently associated with postoperative delirium.…”
Section: Discussionmentioning
confidence: 93%
“…In another prospective study of 485 elderly men undergoing transurethral prostatectomy for benign prostatic hyperplasia, Tai et al 16 showed that patients with a higher Geriatric Depression Scale (GDS) score were significantly more likely to develop postoperative delirium. Similarly, in a retrospective study of 224,060 patients undergoing elective total shoulder arthroplasty between 2002 and 2012, Mollon et al 10 showed depression to be an independent risk factor for postoperative delirium. In another retrospective analysis of 91 patients (age ≥ 75 years) who underwent esophagectomy for the treatment of esophageal cancer, Yamamoto et al 20 showed that GDS score was independently associated with postoperative delirium.…”
Section: Discussionmentioning
confidence: 93%
“…Also, these studies may in more detail inform on whether patients with diagnoses such as sleep apnea and depression that have previously associated with POD should receive focused peri-operative care (Flink et al , 2012, Roggenbach et al , 2014, Mollon et al , 2016, Nadler et al , 2017). These studies may also make clear the extent to which susceptibility to POD as defined by significant deviations in EEG alpha and beta power “norms” may be modified by targeted peri-operative management.…”
Section: Discussionmentioning
confidence: 99%
“…7,16 The relationship between depression and low-back pain is well established, 7 with depressive symptomatology linked to a more than 2-fold increase in the odds of low-back pain in 1 study. 25 Despite this association, as well as the link between depression and adverse outcomes after many types of surgery, 5,21 the impact of depression on outcomes following lumbar fusion has yet to be fully characterized.…”
mentioning
confidence: 99%